Yard with fountain - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a yard with a stone fountain in the center foreground. The house stands at the right of the photograph. The yard is bordered by hedges and a low stone wall. A stone archway serves as an entrance to the yard. A flagpole stands in the background.